Behavioral determinants of household recycling participation: the Portuguese case - Do Valle, P. O.; Reis, E.; Menezes, J.; Rebelo, E. (Environment and Behavior, 2004)
Recycling is an effective resource-recovery mechanism with significant economic and environmental benefits. The success of the Portuguese Integrated System of Packaging Waste Management (SIGRE), managed since 1997 by a private company called SPV, depends on a growing and sustained participation of consumers through the correct separation and disposal of recyclable waste. Within this frame-work, the present research applies different multivariate data analysis techniques to some specific questions of the most recent national survey about recycling behavior with the purpose of identifying factors able to motivate consumers to participate in the selective-collection program. Results suggest differences between recyclers and nonrecyclers concerning specific attitudes toward recycling and also the need of improving the provided logistic service. This research proposes also some guidelines that may be considered in future communication and intervention strategies, designed to promote recycling participation.